Dinamika Lingkungan Sosial Terhadap Perilaku Keagamaan Peserta Didik Perspektif Sosiologi Pendidikan Islam - Rochmatus Saidah; Siti Rofiqoh At-Thobibi (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2026)
This study aims to analyze the influence of the social environment on students’ religious behavior from the perspective of Islamic educational sociology. The social environment includes family, school, and community as the three main pillars in shaping students’ religious character. The research method used is a qualitative approach with a library research design, examining various scientific literature related to Islamic educational sociology and the development of religious behavior. The findings indicate that the social environment plays a significant role in shaping students’ attitudes, values, and religious practices. The family acts as the primary foundation for internalizing religious values, the school as a formal institution strengthens religious understanding and practices through curriculum and religious culture, while the community influences through social interactions and prevailing norms. From the perspective of Islamic educational sociology, religious behavior formation is not merely individual but is also a social construction influenced by the surrounding environment. Therefore, synergy among family, school, and community is essential to create a conducive social environment that enhances students’ religious behavior.